(untitled) (Sociologisk Forskning, 2017)
Over the past 30 years, Sweden has witnessed a growth in criminal gangs. Gun violence among young males is also on the rise and have only recently gained wide political attention. Street gangs and gun violence are two prevalent, partially overlapping phenomena that constitute social challenges. Empirically supported legal, policy and practical frameworks are needed in order to reduce the prevalence of gangs and gang violence in Sweden. The first step is to recognize that gangs and gang violence are an emerging societal problem and to identify its root causes, organizational dimensions, and operational patterns. In this note, Swedish street gangs and gang violence are briefly discussed.